The Construction of English - Gray, J. author. aut Link
XI, 218 p.
Keywords: This book takes the view that ELT global coursebooks, in addition to being curriculum artefacts, are also highly wrought cultural artefacts which seek to make English mean in highly selective ways and it argues that the textual construction (and imaging) of English parallels the processes of commodity promotion more generally.